Dynamics of Emotional State in Mothers of Babies Born Significantly Prematurely (28–31 weeks) - Alesia O. Evmenenko (Национальный психологический журнал, 2025)
Objectives. The aim of this study was to identify the dynamics of emotional state in mothers of infants born significantly prematurely. Study Participants. The long-term study involved 30 women in the situation of giving birth significantly prematurely (28–31 weeks) at the age of 29 to 41 years. Methods. The longitudinal study was conducted in 2 stages: during the first week after the birth of a premature baby and after 12–14 weeks. The following techniques were used in the study: The Perinatal Anxiety Screening Scale — PASS-R in the adaptation of M.A. Korgozha and A.O. Evmenenko, Edinburgh Scale of postpartum depression in the adaptation of G.E. Maso, L.I. Wasserman, M.V. Shamanina, clinical questionnaire for the identification and evaluation of neurotic states by K.K. Yakhin and D.M. Mendelevich. Results. In the emotional state of mothers during the first week after the birth of a significantly premature baby, symptoms of anxiety and specific fears characteristic of the perinatal period are present. After 12–14 weeks, a more pronounced pattern of symptoms is observed. At the second stage of the study, 12–14 weeks after giving birth, the emotional state of women showed symptoms of postpartum depression, asthenia, and autonomic disorders. Conclusions. An analysis of changes in the emotional state of mothers of children born significantly prematurely, including an analysis of symptoms of perinatal anxiety, postpartum depression and asthenia, shows that 12–14 weeks after the birth of the child, mothers have deviations from the average normative values for all the studied indicators. The conducted research substantiates the need for the further study of the indicator dynamics in the emotional state of mothers, taking into account the category of prematurity of children by the time of birth, which will make it possible to identify targets in providing comprehensive medical and psychological assistance to mothers both at the hospital and at the outpatient stage of medical rehabilitation.